Discovery of potent inhibitors of the lysophospholipase autotaxin. Issue 22 (15th November 2016) - Shah, Pritom; Cheasty, Anne; Foxton, Caroline; Raynham, Tony; Farooq, Muddasar; Gutierrez, Irene Farre; Lejeune, Aurore; Pritchard, Michelle; Turnbull, Andrew; Pang, Leon; Owen, Paul; Boyd, Susan; et al.
Graphical abstract: Abstract: The autotaxin– lyso phosphatidic acid (ATX–LPA) axis has been implicated in several disease conditions including inflammation, fibrosis and cancer. This makes ATX an attractive drug target and its inhibition may lead to useful therapeutic agents. Through a high throughput screen (HTS) we identified a series of small molecule inhibitors of ATX which have subsequently been optimized for potency, selectivity and developability properties. This has delivered drug-like compounds such as9v (CRT0273750) which modulate LPA levels in plasma and are suitable for in vivo studies. X-ray crystallography has revealed that these compounds have an unexpected binding mode in that they do not interact with the active site zinc ions but instead occupy the hydrophobic LPC pocket extending from the active site of ATX together with occupying the LPA 'exit' channel.